Implementing the Quantum Teaching to improve Social Studies learning outcomes at Junior High School - Rusabeata, Rusabeata; Saliman, Saliman; Rahman, Rusyda Nasyita (JIPSINDO, 2025)
This research aims to investigate the improvement of learning outcomes of Social Studies in class VIII-D of SMP Negeri 1 Dusun Selatan by the method Quantum Learning. Pre-cycle data shows that the majority of students (61%) are below the Minimum Completion Criteria (KKM) due to passive and unmotivated learning processes. The research uses the Classroom Action Research (CAR) method, which is implemented in two cycles with 31 students. The research stages include gradual interventions, where Cycle I showed initial but not optimal improvements. Based on reflection, corrective actions in Cycle II were refined by optimizing the learning environment through spatial arrangement and music, and strengthening individual accountability through independent worksheets (LKPD) before group discussions. The main findings show a very significant increase in learning outcomes: the number of students in the "High" and "Very High" categories jumped drastically from only 22.5% in the pre-cycle to 84% at the end of Cycle II. It was concluded that the implementation of the adaptive and holistic Quantum Teaching model has proven to be very effective in transforming the learning process and fundamentally improving student learning outcomes.